Polymer dispersant, preparation method, electrode slurry, electrode plate and battery

By designing a polymer dispersant containing imidized five-membered ring structure and carboxylic acid groups, the problems of poor dispersion, high viscosity and short storage time in the preparation of electrode slurry are solved, and the stability of battery quality is improved.

CN119842007APending Publication Date: 2025-04-18SHANGHAI SUNRISE POLYMER MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311803204.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the preparation of electrode slurry, the problems of poor particle dispersion, high slurry viscosity, and short storage time often occur in the prior art, which affects the quality stability of the battery.

Method used

A polymer dispersant is designed with a specific content of imidized five-membered ring structure and carboxylic acid groups prepared by a controlled ring-opening reaction of maleic anhydride ethylene copolymer. This dispersant is used to prepare electrode slurries and has excellent dispersion and viscosity-reducing effects.

Benefits of technology

The dispersion effect and storage stability of the electrode slurry are significantly improved, the storage time of the slurry is extended, and the quality stability of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004629442260000021
    Figure BDA0004629442260000021
  • Figure BDA0004629442260000022
    Figure BDA0004629442260000022
  • Figure BDA0004629442260000023
    Figure BDA0004629442260000023
Patent Text Reader

Abstract

The invention relates to a polymer dispersant, a preparation method, electrode slurry, an electrode plate and a battery. Wherein the polymer dispersant contains a repetitive unit I, a repetitive unit II and a repetitive unit III; the mole number a of the repetitive unit I, the mole number b of the repetitive unit II and the mole number c of the repetitive unit III meet the following quantitative relations: a / (a + b) = 0.50-0.85, and (a + b) / c = 0.2-1.0. The preparation method of the polymer dispersant comprises the following steps: S1, reacting a first raw material at 155-180 DEG C; the first raw material comprises a polymer matrix and a first amine compound; s2, cooling to 60-150 DEG C, continuously adding a second raw material, and reacting; the second raw material comprises the first amine compound or the second amine compound. The preparation method is simple, and the prepared polymer dispersant is novel in structure, can be used in the process of preparing electrode slurry, and has excellent dispersion viscosity reduction and viscosity stabilization effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer dispersant, a preparation method, an electrode slurry, an electrode plate and a battery. Background Art

[0002] In recent years, with the development of new energy storage and electric vehicle fields, carbon materials represented by carbon nanotubes, graphene, and conductive carbon black and carbon-coated materials represented by lithium iron phosphate and lithium iron manganese phosphate have been widely used as battery electrode materials.

[0003] However, due to their special particle structure and surface morphology, such carbon materials and carbon-coated materials often suffer from problems such as poor particle dispersion, high slurry viscosity, and short storage time during the preparation of electrode slurry when no dispersant is used or traditional polyvinyl pyrrolidone dispersants are used, further affecting the quality stability of the battery.

[0004] Patent application CN115322293A discloses a dispersant, a preparation method and its application in the preparation of a carbon nanotube dispersion. In the dispersant preparation method provided in the patent application, the reaction temperature of the maleic anhydride copolymer and the amine is always maintained at 80-150°C. In the obtained polymer, almost all of the maleic anhydride is ring-opened to form amide, which limits the viscosity reducing and stabilizing effects of the dispersant. Summary of the invention

[0005] The present invention overcomes the problems of poor particle dispersion, high slurry viscosity, short storage time, etc. that often occur in the process of preparing electrode slurry in the prior art, and provides a polymer dispersant, a preparation method, an electrode slurry, an electrode plate, and a battery. The preparation method of the present invention is simple, and the obtained polymer dispersant has a novel structure, can be used in the process of preparing electrode slurry, and has excellent dispersion, viscosity reduction, and viscosity stabilization effects.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a polymer dispersant comprising a repeating unit I, a repeating unit II and a repeating unit III;

[0008] The structure of the repeating unit I is shown in Formula I:

[0009]

[0010] In each repeating unit I,

[0011] R1 and R2 are each independently hydrogen, methyl or ethyl;

[0012] R3 is each independently C 10 -C 25An alkyl group or a group represented by formula (1);

[0013]

[0014] In each group represented by formula (1), R4, R5, R6, and R7 are each independently hydrogen, methyl, or ethyl; and R8 are each independently C1-C 18 An alkyl group; n is independently 6-60;

[0015] The structure of the repeating unit II is shown in Formula II:

[0016]

[0017] In each repeating unit II,

[0018] R9, R 10 are independently hydrogen, C1-C 25 alkyl or R3; and R9 and R 10 Not at the same time hydrogen;

[0019] Z is each independently hydrogen, Li + 、Na + , K + NH4 + or organic amine groups with a molecular weight of less than 150;

[0020] The structure of the repeating unit III is shown in Formula III:

[0021]

[0022] In each repeating unit III,

[0023] R 11 , R 12 , R 13 are each independently hydrogen, methyl or ethyl;

[0024] R 14 are independently hydrogen, phenyl, C1-C 18 Alkyl or C1-C 18 Alkoxyl groups;

[0025] Wherein, the degree of polymerization a of the repeating unit I, the degree of polymerization b of the repeating unit II, and the degree of polymerization c of the repeating unit III satisfy the following quantitative relationship:

[0026] a / (a+b)=0.50~0.85, (a+b) / c=0.2~1.0.

[0027] In the present invention, "in each ..., ... are each independently ..." means that in the molecular chain of the polymer dispersant, in different repeating units represented by the same general formula, the groups represented by the same symbol may be the same or different.

[0028] For example, "In each repeating unit I, R1 and R2 are independently hydrogen, methyl or ethyl" means that in the molecular chain of the polymer dispersant, in different repeating units I represented by formula (I), R1 may be the same or different, and R2 may be the same or different; in the same repeating unit I, the selection of R1 and R2 does not affect each other and may be the same or different. Similarly, each repeating unit II and each repeating unit III have the above meanings.

[0029] For another example, it is also necessary to explain that "in each group represented by formula (1), R4, R5, R6, and R7 are each independently hydrogen, methyl, or ethyl; R8 is each independently C1-C 18 alkyl; n is independently 6-60" means that in the molecular chain of the polymer dispersant, in different repeating units I represented by formula (I), when R3 is a group represented by formula (1), "n" in formula (1) may be the same or different; n In the above, R4, R5, R6, and R7 may be the same or different.

[0030] In the present invention, in each repeating unit I, R3 can be independently C 12 -C 18 Alkyl groups, such as C 12 Alkyl, C 16 Alkyl or C 18 of alkyl.

[0031] In the present invention, in each repeating unit II, R9, R 10 Can be independently C 18 of alkyl.

[0032] In the present invention, the weight average molecular weight of the polymer dispersant may be 16000-52000, for example, 16800, 20200, 21900, 23400, 26500, 27800, 29700, 35900 or 51200.

[0033] In the present invention, the molecular weight distribution index (PDI) of the polymer dispersant may be no greater than 2.00, for example, 1.59, 1.60, 1.62, 1.63, 1.65, 1.75, 1.78 or 1.92.

[0034] In the present invention, the distribution of the repeating unit I, the repeating unit II and the repeating unit III may be one of the following:

[0035] ① The repeating unit I, the repeating unit II and the repeating unit III are randomly distributed;

[0036] ② The repeating unit I and the repeating unit II form a first block, and the repeating unit III forms a second block. In the first block, the repeating unit I and the repeating unit II are randomly distributed.

[0037] In the present invention, the degree of polymerization means the average value of the number of repeating units represented by the same general formula in the molecular chain of the polymer dispersant. For example, the meaning of "the degree of polymerization a of the repeating unit I" means that the average value of the number of repeating units I represented by formula (I) in the molecular chain of the polymer dispersant is a.

[0038] In the present invention, the value of a / (a+b) may be 0.55, 0.66, 0.70, 0.73, 0.77, 0.81 or 0.82.

[0039] In the present invention, the value of (a+b) / c may be 0.30, 0.39, 0.42 or 0.76.

[0040] In the present invention, the degree of polymerization a of the repeating unit I may be 1-100.

[0041] In the present invention, the degree of polymerization b of the repeating unit II may be 1-100.

[0042] In the present invention, the degree of polymerization c of the repeating unit III may be 10-200.

[0043] In a second aspect, the present invention provides a method for preparing a polymer dispersant, comprising the following steps:

[0044] S1. The first raw material is reacted at 155-180°C; the first raw material comprises a base polymer and a first amine compound;

[0045] S2. Cooling to 60-150°C, continuing to add the second raw material, reacting; the second raw material comprises the first amine compound or the second amine compound;

[0046] The first raw material and / or the second raw material further comprises a third amine compound;

[0047] The structure of the matrix polymer is shown in Formula M-1:

[0048]

[0049] in,

[0050] R1, R2, R 11 , R12 , R 13 and R 14 R1, R2, R 11 , R 12 , R 13 and R 14 ;

[0051] The ratio of d to e is (0.2-1.0):1;

[0052] The structure of the first amine compound is shown in Formula M-2:

[0053] H2N—R3

[0054] M-2

[0055] Wherein, R3 is R3 as described above;

[0056] The structure of the second amine compound is shown in Formula M-3:

[0057]

[0058] Among them, R9 and R 10 R9 and R as mentioned above 10 ;

[0059] The structure of the third amine compound is shown in Formula M-4:

[0060]

[0061] wherein R4, R5, R6, R7, R8 and n are as described above.

[0062] In the present invention, d may be 2-200.

[0063] In the present invention, e may be 10-200.

[0064] In the present invention, the number average molecular weight of the matrix polymer can be conventionally selected in the art, preferably 2000-3800, such as 2000, 3000 or 3800.

[0065] In the present invention, the acid value of the base polymer can be selected conventionally in the art, preferably 285-660 mgKOH / g, such as 285 mgKOH / g, 355 mgKOH / g, 480 mgKOH / g or 660 mgKOH / g.

[0066] In the present invention, the base polymer can be selected conventionally in the art, preferably maleic anhydride ethylene copolymer, SMA1000P, SMA2000P or SMA3000P.

[0067] In the present invention, the total amine value of the first amine compound can be selected conventionally in the art, preferably 210-300 mgKOH / g, such as 210 mgKOH / g, 223 mgKOH / g or 300 mgKOH / g.

[0068] In the present invention, the first amine compound may be a primary amine.

[0069] The primary amine can be selected conventionally in the art, preferably dodecyl primary amine, hexadecyl primary amine or octadecyl primary amine.

[0070] In the present invention, the total amine value of the second amine compound can be selected conventionally in the art, preferably 108 mgKOH / g.

[0071] In the present invention, the second amine compound may be a secondary amine.

[0072] The secondary amine can be selected conventionally in the art, preferably dioctadecylamine.

[0073] In the present invention, the third amine compound may be a polyetheramine.

[0074] The polyetheramine may be an alkyl-terminated monofunctional polyetheramine, preferably, the polyetheramine may be an alkoxy polyethylene glycol polyetheramine, an alkoxy polypropylene glycol polyetheramine, an alkoxy polyethylene glycol polypropylene glycol random polyetheramine or an alkoxy polyethylene glycol polypropylene glycol block polyetheramine; for example, the polyetheramine JEFFAMINE L100, the polyetheramine JEFFAMINE B60 or the polyetheramine JEFFAMINE B200 of Huntsman Corporation of the United States.

[0075] In the present invention, conventionally, the reaction of step S1 and step S2 is carried out in a solvent, and the solvent can be any organic solvent applicable in the art, such as N-methylpyrrolidone (NMP). The amount of the solvent can be selected according to the applicable range in the art.

[0076] In step S1, the reaction temperature may be 158°C, 160°C, 165°C, 168°C, 175°C or 180°C.

[0077] In step S1, the reaction time is preferably 1.5-3 h, such as 1.5 h, 2 h, 2.5 h or 3 h, until the reaction is completed.

[0078] In step S1, during the reaction, a protective gas may be used to remove the water generated by the reaction, wherein the protective gas refers to a gas that does not react with the reaction system, such as nitrogen or an inert gas.

[0079] In step S2, the reaction temperature may be 80°C, 85°C, 90°C, 105°C, 110°C, 115°C, 120°C, 135°C or 140°C.

[0080] In step S2, the reaction time is preferably 2-3 hours until the reaction is completed.

[0081] In certain specific embodiments, the reaction temperature in step S1 is 158-165°C, and the reaction temperature in step S2 is 135-140°C.

[0082] In certain specific embodiments, the reaction temperature in step S1 is 168-175°C, and the reaction temperature in step S2 is 115-120°C.

[0083] In certain specific embodiments, the reaction temperature in step S1 is 175-180°C, and the reaction temperature in step S2 is 105-110°C.

[0084] In certain specific embodiments, the reaction temperature in step S1 is 160-165°C, and the reaction temperature in step S2 is 85-90°C.

[0085] In certain specific embodiments, the reaction temperature in step S1 is 160-165°C, and the reaction temperature in step S2 is 80-90°C.

[0086] In certain specific embodiments, the reaction temperature in step S1 is 160-165°C, and the reaction temperature in step S2 is 105-110°C.

[0087] In a third aspect, the present invention provides a polymer dispersant obtained by the preparation method of the polymer dispersant as described above.

[0088] In a fourth aspect, the present invention provides an electrode slurry comprising an electrode material and the polymer dispersant as described above.

[0089] In the present invention, the electrode material may be a carbon material or a carbon-coated material.

[0090] The carbon material may be selected conventionally in the art, such as one or more of carbon nanotubes, graphene, acetylene black, porous carbon and conductive carbon black.

[0091] Wherein, the carbon-coated material is one or both of carbon-coated lithium iron phosphate and carbon-coated lithium manganese iron phosphate.

[0092] Wherein, the electrode slurry may include: the polymer dispersant, the carbon material and a viscosity reducer.

[0093] The viscosity reducer can be a conventional choice in the art, such as the D603 product of Ruigu New Energy (Shanghai) Material Technology Co., Ltd.

[0094] The mass ratio of the polymer dispersant, the carbon material and the viscosity reducer may be (2-8):1:(0.05-0.5), for example 4:1:0.1.

[0095] Wherein, the electrode slurry may include: the polymer dispersant, the carbon coating material, a binder and a conductive agent.

[0096] The binder can be selected conventionally in the art, such as PVDF.

[0097] The conductive agent can be selected from conventional ones in the art, such as carbon nanotubes, conductive carbon black (SP), acetylene black, and the like.

[0098] The mass ratio of the polymer dispersant, the carbon coating material, the binder and the conductive agent may be (0.2-0.8):173.70:(3-4):(2-3), for example, 0.35:173.70:3.6:2.7.

[0099] In a fifth aspect, the present invention provides an electrode plate, which is made using the electrode slurry as described above.

[0100] In the present invention, the method for preparing an electrode plate using the electrode slurry can be conventional in the art, and generally comprises: coating the electrode slurry on at least one surface of a current collector, and drying.

[0101] In a sixth aspect, the present invention provides a battery comprising the electrode plate as described above.

[0102] In the present invention, the battery is preferably a lithium ion battery.

[0103] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention. The reagents and raw materials used in the present invention are all commercially available.

[0104] The positive and progressive effects of the present invention are:

[0105] The present invention designs the structure of the repeating unit in the molecular chain of the polymer dispersant, and specifically can obtain a polymer dispersant with a novel structure based on a controllable ring-opening reaction of maleic anhydride ethylene copolymer. The molecular chain of the polymer dispersant contains a specific content of an imidized five-membered ring structure and a specific content of a carboxylic acid group. On the one hand, compared with a conventional non-cyclic structure, the imidized five-membered ring structure has better stability and better adsorption effect on carbon materials, and is more suitable for application in electrode slurries; on the other hand, the carboxylic acid group can further improve the dispersion effect. Based on this, the polymer dispersant of the present invention is used in the process of preparing electrode slurries, and has excellent dispersion, viscosity reduction and viscosity stabilization effects. DETAILED DESCRIPTION

[0106] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0107] In the following synthesis examples and comparative synthesis examples:

[0108] (1) Weight average molecular weight and molecular weight distribution index (PDI)

[0109] The weight average molecular weight and molecular weight distribution index of the polymer are tested by using a Waters 1515 gel permeation chromatograph, calibrated with standard polystyrene, and using N-methylpyrrolidone as the mobile phase at a column temperature of about 90°C.

[0110] (2) Solid content

[0111] Solid content refers to the mass percentage of solids in a slurry or solution.

[0112] (3) Imidization rate

[0113] Calculation method of imidization rate:

[0114] Imidization rate = (number of moles of carboxylic acid in the starting material - number of moles of carboxylic acid in the reaction product - number of moles of primary amine in the reaction material) / number of moles of primary amine in the reaction material × 100%

[0115] The main raw materials used in the following synthesis examples and comparative synthesis examples are shown in Table 1:

[0116] Table 1

[0117]

[0118] Synthesis Example 1

[0119] S1. Add 1640.0g NMP to a 3000ml four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, and a feeding device, start stirring, add 400.0g (about 0.20mol) SMA1000P, and heat to less than 150°C to completely dissolve SMA1000P. Add 185.4g (about 1.00mol) of pre-heated and melted dodecyl primary amine, and raise the temperature to 158°C; maintain the reaction temperature at 158-165°C, add 300.0g (about 0.30mol) of pre-heated and melted polyetheramine JEFFAMINE L100, and keep the temperature for 3 hours, and remove the water generated by the imidization reaction by nitrogen.

[0120] S2. Then, the temperature of the reaction material is lowered to 135-140° C., and 208.8 g (about 0.40 mol) of pre-heated and melted dioctadecylamine is added. After the reaction is kept warm for 2 hours, the temperature is lowered and the material is discharged to obtain a polymer solution containing the polymer dispersant P-1, with a solid content of 40% and an imidization rate of 92%.

[0121] The weight average molecular weight of the polymer dispersant P-1 was 21,900, and the molecular weight distribution index (PDI) was 1.60.

[0122] Synthesis Example 2

[0123] S1. Add 1950.0g NMP to a 3000ml four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, and a feeding device, start stirring, add 400.0g (about 0.40mol) SMA1000P, and heat to less than 150°C to completely dissolve SMA1000P. Add 193.2g (about 0.8mol) hexadecyl primary amine that was heated and melted in advance, and raise the temperature to 158°C; then add 500.0g (0.50mol) polyetheramine JEFFAMINE L100 that was heated and melted in advance, raise the temperature to 168-175°C and keep the temperature for reaction for 2 hours, and remove the water generated by the imidization reaction with nitrogen.

[0124] S2. Then, the temperature of the reaction material is lowered to 115-120° C., and 208.8 g (about 0.40 mol) of pre-heated and melted dioctadecylamine is added. After the reaction is continued for 2 hours, the temperature is lowered and the material is discharged to obtain a polymer solution containing the polymer dispersant P-2, with a solid content of 40% and an imidization rate of 95%.

[0125] The weight average molecular weight of the polymer dispersant P-2 was 26,500, and the molecular weight distribution index (PDI) was 1.62.

[0126] Synthesis Example 3

[0127] S1. Add 1700.0g NMP to a 3000ml four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a feeding device, start stirring, add 400.0g (about 0.40mol) SMA1000P, and heat to less than 150°C to completely dissolve SMA1000P. Add 215.6g (about 0.80mol) octadecyl primary amine that has been heated and melted in advance; then add 360.0g (about 0.60mol) polyetheramine JEFFAMINE B60, heat to 175-180°C and keep warm for 1.5 hours, and remove the water generated by the imidization reaction with nitrogen.

[0128] S2. Then, the temperature of the reaction material is lowered to 105-110° C., 156.6 g (about 0.30 mol) of pre-heated and melted dioctadecylamine is added, and the reaction is continued for 2 hours. Then, the temperature is lowered and the material is discharged to obtain a polymer solution containing polymer dispersant P-3, with a solid content of 40% and an imidization rate of 98%.

[0129] The weight average molecular weight of the polymer dispersant P-3 was 23,400, and the molecular weight distribution index (PDI) was 1.65.

[0130] Synthesis Example 4

[0131] S1. Add 1700.0g NMP to a 3000ml four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a feeding device, start stirring, add 333.3g (about 0.17mol) SMA1000P, and heat to less than 150°C to completely dissolve SMA1000P. Add 161.0g (about 0.67mol) hexadecyl primary amine that has been heated and melted in advance; then add 333.3g (about 0.17mol) polyetheramine JEFFAMINE B200, heat to 160-165°C and keep warm for 2.5 hours, and remove the water generated by the imidization reaction with nitrogen.

[0132] S2. Then, the temperature of the reaction material is lowered to 85-90° C., 304.5 g (about 0.58 mol) of pre-heated and melted dioctadecylamine is added, and the reaction is continued for 3 hours. Then, the temperature is lowered and the material is discharged to obtain a polymer solution containing polymer dispersant P-4, with a solid content of 40% and an imidization rate of 94%.

[0133] The weight average molecular weight of the polymer dispersant P-4 was 27,800, and the molecular weight distribution index (PDI) was 1.63.

[0134] Synthesis Example 5

[0135] S1. Add 1470.0g NMP to a 3000ml four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, and a feeding device, start stirring, add 400.0g (about 0.40mol) SMA1000P, and heat to less than 150°C to completely dissolve SMA1000P. Add 222.5g (about 1.20mol) of dodecyl primary amine that has been heated and melted in advance; heat to 160-165°C and keep warm for 2.5 hours, and remove the water generated by the imidization reaction with nitrogen.

[0136] S2. Then, the temperature of the reaction material is lowered to 80-90° C., 156.6 g (about 0.30 mol) of dioctadecylamine and 200.0 g (about 0.20 mol) of polyetheramine JEFFAMINE L100 which are heated and melted in advance are added, and the reaction is continued for 3 hours, and then the temperature is lowered and the material is discharged to obtain a polymer solution containing polymer dispersant P-5, whose solid content is 40% and imidization rate is 94%.

[0137] The weight average molecular weight of the polymer dispersant P-5 was 16,800, and the molecular weight distribution index (PDI) was 1.59.

[0138] Synthesis Example 6

[0139] S1. Add 1450.0g NMP to a 3000ml four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a feeding device, start stirring, add 400.0g (about 0.40mol) SMA1000P, and heat to less than 150°C to completely dissolve SMA1000P. Add 241.0g (about 1.30mol) of dodecyl primary amine that has been heated and melted in advance; then add 300.0g (about 0.30mol) of polyetheramine JEFFAMINE L100, heat to 160-165°C and keep warm for 2.0 hours, and remove the water generated by the imidization reaction with nitrogen.

[0140] S2. Then, the temperature of the reaction material is lowered to 105-110° C., and 27.0 g (about 0.10 mol) of octadecyl primary amine which has been heated and melted in advance is added. After the reaction is continued for 2 hours, the temperature is lowered and the material is discharged to obtain a polymer solution containing polymer dispersant P-6, with a solid content of 40% and an imidization rate of 82%.

[0141] The weight average molecular weight of the polymer dispersant P-6 was 20200, and the molecular weight distribution index (PDI) was 1.62.

[0142] Synthesis Example 7

[0143] S1. Add 1980.0g NMP to a 3000ml four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a feeding device, start stirring, add 600.0g (about 0.20mol) SMA2000P, and heat to less than 150°C to completely dissolve SMA2000P. Add 265.7g (about 1.10mol) hexadecyl primary amine that has been heated and melted in advance; then add 300.0g (about 0.30mol) polyetheramine JEFFAMINE L100, heat to 160-165°C and keep warm for 2.5 hours, and remove the water generated by the imidization reaction with nitrogen.

[0144] S2. Then, the temperature of the reaction material is lowered to 105-110° C., and 156.6 g (about 0.30 mol) of pre-heated and melted dioctadecylamine is added. After the reaction is continued for 3 hours, the temperature is lowered and the material is discharged to obtain a polymer solution containing the polymer dispersant P-7, with a solid content of 40% and an imidization rate of 93%.

[0145] The weight average molecular weight of the polymer dispersant P-7 was 29,700, and the molecular weight distribution index (PDI) was 1.75.

[0146] Synthesis Example 8

[0147] S1. Add 1900.0g NMP to a 3000ml four-necked flask equipped with a stirrer, a thermometer, a reflux condenser, and a feeding device, start stirring, add 633.3g (about 0.17mol) SMA3000P, and heat to less than 150°C to completely dissolve SMA3000P. Add 201.3g (about 0.83mol) hexadecyl primary amine that has been heated and melted in advance; then add 250.0g (about 0.25mol) polyetheramine JEFFAMINE L100, heat to 160-165°C and keep warm for 2.5 hours, and remove the water generated by the imidization reaction with nitrogen.

[0148] S2. Then, the temperature of the reaction material is lowered to 105-110° C., and 174.0 g (about 0.33 mol) of pre-heated and melted dioctadecylamine is added. After the reaction is continued for 3 hours, the temperature is lowered and the material is discharged to obtain a polymer solution containing polymer dispersant P-8, with a solid content of 40% and an imidization rate of 92%.

[0149] The weight average molecular weight of the polymer dispersant P-8 was 35,900, and the molecular weight distribution index (PDI) was 1.78.

[0150] Synthesis Example 9

[0151] S1. Add 1900.0g NMP into a 3000ml four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a feeding device, start stirring, add 300.0g (about 0.10mol) of maleic anhydride ethylene copolymer, and heat to less than 150°C to completely dissolve the maleic anhydride ethylene copolymer. Add 241.5g (about 1.00mol) of hexadecyl primary amine that has been heated and melted in advance; then add 300.0g (about 0.30mol) of polyetheramine JEFFAMINE L100, heat to 160-165°C and keep warm for 2.5 hours, and remove the water generated by the imidization reaction with nitrogen.

[0152] S2. Then, the temperature of the reaction material is lowered to 105-110° C., and 234.9 g (about 0.45 mol) of pre-heated and melted dioctadecylamine is added. After the reaction is continued for 3 hours, the temperature is lowered and the material is discharged to obtain a polymer solution containing the polymer dispersant P-9, with a solid content of 40% and an imidization rate of 94%.

[0153] The weight average molecular weight of the polymer dispersant P-9 was 51,200, and the molecular weight distribution index (PDI) was 1.92.

[0154] Comparative Synthesis Example 1

[0155] Compared with Synthesis Example 3, the only difference is that octadecyl primary amine is replaced with an equal molar amount of n-octylamine, the obtained polymer is labeled S-1, and the imidization rate is 98%. The weight average molecular weight of the polymer dispersant S-1 is 22700, and the molecular weight distribution index (PDI) is 1.64.

[0156] Comparative Synthesis Example 2

[0157] Compared with Synthesis Example 3, the only difference is that the reaction temperature is controlled at 105-110°C throughout the process, the obtained polymer is labeled S-2, and the imidization rate is 8%. The weight average molecular weight of the polymer dispersant S-2 is 22100, and the molecular weight distribution index (PDI) is 1.63.

[0158] Comparative Synthesis Example 3

[0159] Compared with Synthesis Example 6, the only difference is that the reaction temperature is controlled at 160-165°C throughout the process, the obtained polymer is labeled S-3, and the overall imidization rate is measured to be 97% at the end of the reaction. The weight average molecular weight of the polymer dispersant S-3 is 21100, and the molecular weight distribution index (PDI) is 1.64.

[0160] Comparative Synthesis Example 4

[0161] The polymer dispersant S-4 was prepared according to Example 2 of Chinese invention patent CN115322293A. At the end of the reaction, the overall imidization rate was 12%, which was marked as S-4. The weight average molecular weight of the polymer dispersant S-4 was 27100 and the molecular weight distribution index (PDI) was 1.62.

[0162] The main raw materials and process parameters of the synthesis examples and comparative examples are summarized in Table 2, and some characteristic parameters of the prepared polymer dispersants are shown in Table 3:

[0163] Table 2

[0164]

[0165]

[0166] Table 3

[0167]

[0168] Application example 1: Electrode slurry containing carbon nanotubes (CNT)

[0169] Carbon nanotubes G (CNT) are used, and their main technical indicators are shown in Table 4.

[0170] Table 4 Technical indicators of carbon nanotubes G (CNT)

[0171] project Specific surface area Pipe diameter length purity Fe content Test Results <![CDATA[280m 2 / g]]> 7-15nm <50μm ≥98.5% ≤500ppm

[0172] Use a sand mill to grind and disperse according to the mass ratio of CNT: polymer dispersant (effective part): viscosity reducer: NMP = 4.0%: 1.0%: 0.1%: 94.9%, and grind for 3 hours after all CNTs are added to obtain an electrode slurry containing CNT (referred to as CNT slurry). Among them, the polymer dispersant is the polymer dispersant obtained in Synthesis Examples 1-9 and Synthesis Comparative Examples 1-4 and the conventional dispersant PVP K30, and the corresponding electrode slurries obtained are respectively recorded as CNT-01 to CNT-14, as shown in Table 5. The viscosity reducer uses the D603 product from Ruigu New Energy (Shanghai) Materials Technology Co., Ltd.

[0173] The rotational viscosity was then tested using a rotational viscometer 1 h, 24 h, 3 days, 7 days, 14 days, and 30 days after grinding. The results are shown in Table 5.

[0174] Reference standard: GB / T 10247-2008 viscosity test method, instrument model: DV-2TLV Brookfield viscometer, key parameters are as follows:

[0175] Rotor: selected according to viscosity range; rotation speed: 60rpm; time: 3min; test temperature: 25℃.

[0176] Table 5 Rotational viscosity of CNT slurry after storage for different time periods (viscosity unit: mPa·s)

[0177] CNT slurry Dispersant Type 1h 24h 3 days 7 days 14 days 28 days CNT-01 P-1 1500 2470 3750 4650 4230 4430 CNT-02 P-2 1430 1960 2860 2640 3290 3350 CNT-03 P-3 740 1170 1502 2070 2810 3490 CNT-04 P-4 528 1066 1378 2380 2060 2290 CNT-05 P-5 1490 2780 3620 4070 3340 3410 CNT-06 P-6 1312 2200 2820 3010 3150 3650 CNT-07 P-7 1820 2760 3660 4370 5130 5930 CNT-08 P-8 1580 2100 2910 3270 3900 2940 CNT-09 P-9 2050 4060 4420 5170 5070 4210 CNT-10 S-1 7400 9180 10020 10360 18470 25400 CNT-11 S-2 3050 5500 6710 6900 7120 7420 CNT-12 S-3 3550 4520 5760 6410 6820 7110 CNT-13 S-4 3110 5680 6120 6540 6770 7500 CNT-14 PVP K30* 5640 8710 9220 8680 7860 7390

[0178] Note: PVP K30 adopts Luvitec K30 produced by BASF GmbH of Germany.

[0179] From the data comparison of CNT-03 slurry and CNT-10 slurry, it can be seen that when preparing the polymer dispersant in CNT-10 slurry, the primary amine in Synthesis Comparative Example 1 uses n-octylamine, that is, the carbon chain length is only 8, which is lower than the carbon chain length of R3 in Synthesis Example 3, and it is difficult to achieve the effect of viscosity reduction and viscosity stabilization.

[0180] From the data comparison of CNT-03 slurry and CNT-11 slurry, it can be seen that when preparing the polymer dispersant in CNT-11 slurry, the reaction temperature of 105-110°C was used in all synthetic comparative examples 2, resulting in a small number of repeating units with a five-membered ring structure, resulting in very limited improvements in the viscosity reduction and viscosity stabilization effects.

[0181] From the data comparison of CNT-06 slurry and CNT-12 slurry, it can be seen that when preparing the polymer dispersant in CNT-12 slurry, the reaction temperature of 160-165°C was used in all synthetic comparative examples 3, resulting in an excessive number of repeating units with a five-membered ring structure, resulting in very limited improvements in the viscosity reduction and viscosity stabilization effects.

[0182] In summary, from the results in Table 5, it can be seen that the viscosity reduction and viscosity stabilization effects of CNT-01 to CNT-09 prepared using the polymer dispersant of the present invention are significantly better than those of CNT-10 to CNT-14 prepared using the comparative dispersant.

[0183] Application Example 2: Electrode slurry containing carbon-coated lithium iron phosphate (C@LFP)

[0184] The lithium iron phosphate product 10P (C@LFP) is used, and its main technical indicators are shown in Table 6.

[0185] Table 6 Technical indicators of lithium iron phosphate products 10P

[0186] project Specific surface area D50 D90 Carbon content pH First charge capacity First discharge capacity Test Results <![CDATA[13.1m 2 / g]]> 1.26μm 4.28μm 1.15% 9.0 161.9mAh / g 156.3mAh / g

[0187] A homogenizer was used to perform homogenization and dispersion according to the scheme in Table 7 to obtain an electrode slurry containing C@LFP (referred to as C@LFP slurry). The polymer dispersant was the polymer dispersant obtained in Synthesis Examples 1-9 and Comparative Synthesis Examples 1-4 and a conventional dispersant PVP K30, and the numbers of the corresponding electrode slurries obtained were shown in Table 7.

[0188] The rotational viscosity was then tested after 1 hour of discharge and 24 hours of storage. The results are shown in Table 8.

[0189] Reference standard: GB / T 10247-2008 viscosity test method, instrument model: DV-2TLV Brookfield viscometer, key parameters are as follows:

[0190] Rotor: selected according to viscosity range; rotation speed: 60rpm; time: 3min; test temperature: 25℃.

[0191] Table 7 Homogenization scheme of C@LFP slurry

[0192]

[0193] Table 8 Rotational viscosity of C@LFP slurry

[0194] C@LFP slurry number 1h rotational viscosity, mPa·s 24h rotational viscosity, mPa·s 10P-0 10200 47500 10P-P1 7560 12000 10P-P2 6640 10440 10P-P3 6580 10820 10P-P4 6200 10660 10P-P5 5720 9520 10P-P6 6980 10940 10P-P7 6900 10840 10P-P8 6840 11780 10P-P9 7560 12080 10P-S1 12060 26300 10P-S2 12780 22950 10P-S3 12500 26600 10P-S4 11650 21800 10P-K30 18500 43200

[0195] From the data comparison of 10P-P3 slurry and 10P-S1 slurry, it can be seen that when preparing the polymer dispersant in 10P-S1 slurry, the primary amine in Synthesis Comparative Example 1 uses n-octylamine, that is, the carbon chain length is only 8, which is lower than the carbon chain length of R3 in Synthesis Example 3, and it is difficult to achieve the effect of viscosity reduction and viscosity stabilization.

[0196] From the data comparison of 10P-P3 slurry and 10P-S2 slurry, it can be seen that when preparing the polymer dispersant in 10P-S2 slurry, the reaction temperature of 105-110°C was used in all synthetic comparative examples 2, resulting in a small number of repeating units with a five-membered ring structure, resulting in very limited improvements in the viscosity reduction and viscosity stabilization effects.

[0197] From the data comparison of 10P-P6 slurry and 10P-S3 slurry, it can be seen that when preparing the polymer dispersant in 10P-S3 slurry, the reaction temperature of 160-165°C was used in all synthetic comparative examples 3, resulting in an excessive number of repeating units with a five-membered ring structure, resulting in very limited improvements in the viscosity reduction and viscosity stabilization effects.

[0198] In summary, it can be seen from the results in Table 8 that the viscosity reduction and viscosity stabilization effects of 10P-P1 to 10P-P9 slurries prepared by the dispersant of the present invention are significantly better than those of 10P-K30, 10P-S1 to 10P-S4 prepared by the comparative dispersant. The present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but it does not mean that the present invention must rely on the above-mentioned embodiments. The embodiments in this section are only exemplary and explanatory and should not have any limiting effect on the scope of protection of the present invention.

Claims

1. A polymer dispersant, characterized in that It contains repeating unit I, repeating unit II and repeating unit III; The structure of the repeating unit I is shown in Formula I: In each repeating unit I, R1 and R2 are each independently hydrogen, methyl or ethyl; R3 is each independently C 10 -C 25 An alkyl group or a group represented by formula (1); In each group represented by formula (1), R4, R5, R6, and R7 are each independently hydrogen, methyl, or ethyl; and R8 are each independently C1-C 18 An alkyl group; n is independently 6-60; The structure of the repeating unit II is shown in Formula II: In each repeating unit II, R9, R 10 are independently hydrogen, C1-C 25 alkyl or R3; and R9 and R 10 Not at the same time hydrogen; Z is each independently hydrogen, Li + 、Na + , K + NH4 + or organic amine groups with a molecular weight of less than 150; The structure of the repeating unit III is shown in Formula III: In each repeating unit III, R 11 , R 12 , R 13 are each independently hydrogen, methyl or ethyl; R 14 are independently hydrogen, phenyl, C1-C 18 Alkyl or C1-C 18 Alkoxyl groups; Wherein, the degree of polymerization a of the repeating unit I, the degree of polymerization b of the repeating unit II, and the degree of polymerization c of the repeating unit III satisfy the following quantitative relationship: a / (a+b)=0.50~0.85, (a+b) / c=0.2~1.

0.

2. The polymer dispersant according to claim 1, characterized in that In each repeating unit I, R3 is independently C 12 -C 18 Alkyl groups, such as C 12 Alkyl, C 16 Alkyl or C 18 The alkyl group; And / or, in each repeating unit II, R9, R 10 Each independently is C 18 The alkyl group; and / or, the polymer dispersant has a weight average molecular weight of 16,000-52,000, such as 16,800, 20,200, 21,900, 23,400, 26,500, 27,800, 29,700, 35,900 or 51,200; and / or, the polymer dispersant has a PDI of no greater than 2.00, e.g., 1.59, 1.60, 1.62, 1.63, 1.65, 1.75, 1.78, or 1.92; And / or, the distribution of the repeating unit I, the repeating unit II and the repeating unit III is one of the following: ① The repeating unit I, the repeating unit II and the repeating unit III are randomly distributed; ② The repeating unit I and the repeating unit II form a first block, and the repeating unit III forms a second block, and in the first block, the repeating unit I and the repeating unit II are randomly distributed; and / or the value of a / (a+b) is 0.55, 0.66, 0.70, 0.73, 0.77, 0.81 or 0.82; and / or, the value of (a+b) / c is 0.30, 0.39, 0.42 or 0.76; And / or, the degree of polymerization a of the repeating unit I is 1-100; And / or, the degree of polymerization b of the repeating unit II is 1-100; And / or, the degree of polymerization c of the repeating unit III is 10-200.

3. A method for preparing a polymer dispersant, characterized in that: It includes the following steps: S1. The first raw material is reacted at 155-180°C; the first raw material comprises a base polymer and a first amine compound; S2. Cooling to 60-150°C, continuing to add the second raw material, reacting; the second raw material comprises the first amine compound or the second amine compound; The first raw material and / or the second raw material further comprises a third amine compound; The structure of the matrix polymer is shown in Formula M-1: in, R1, R2, R 11 , R 12 , R 13 and R 14 As defined in claim 1 or 2; The ratio of d to e is (0.2-1.0):1; The structure of the first amine compound is shown in Formula M-2: H2N—R3 M-2 Wherein, R3 is as defined in claim 1 or 2; The structure of the second amine compound is shown in Formula M-3: Among them, R9 and R 10 As defined in claim 1 or 2; The structure of the third amine compound is shown in Formula M-4: wherein R4, R5, R6, R7, R8 and n are as defined in claim 1 or 2.

4. The method for preparing a polymer dispersant according to claim 3, characterized in that: d is 2-200; and / or, e is 10-200; and / or, the number average molecular weight of the matrix polymer is 2000-3800, such as 2000, 3000 or 3800; and / or, the acid value of the base polymer is 285-660 mgKOH / g, such as 285 mgKOH / g, 355 mgKOH / g, 480 mgKOH / g or 660 mgKOH / g; and / or, the matrix polymer is maleic anhydride ethylene copolymer, SMA1000P, SMA2000P or SMA3000P; and / or, the total amine value of the first amine compound is 210-300 mgKOH / g, such as 210 mgKOH / g, 223 mgKOH / g or 300 mgKOH / g; And / or, the first amine compound is a primary amine; the primary amine is preferably dodecyl primary amine, hexadecyl primary amine or octadecyl primary amine; and / or, the total amine value of the second amine compound is 108 mgKOH / g; And / or, the second amine compound is a secondary amine; the secondary amine is preferably dioctadecylamine; And / or, the third amine compound is a polyetheramine; the polyetheramine is preferably an alkyl-terminated monofunctional polyetheramine, and the polyetheramine is preferably an alkoxy polyethylene glycol polyetheramine, an alkoxy polypropylene glycol polyetheramine, an alkoxy polyethylene glycol polypropylene glycol random polyetheramine or an alkoxy polyethylene glycol polypropylene glycol block polyetheramine.

5. The method for preparing a polymer dispersant according to claim 3, characterized in that: The reaction of step S1 and step S2 is carried out in a solvent, and the solvent is preferably NMP; And / or, in step S1, the reaction time is 1.5-3 h, for example 1.5 h, 2 h, 2.5 h or 3 h; And / or, in step S1, during the reaction, a protective gas is used to remove water generated by the reaction; the protective gas is preferably nitrogen or an inert gas; And / or, in step S2, the reaction time is 2-3h; And / or, the temperature of the reaction in step S1 and the temperature of the reaction in step S2 satisfy any one of the following conditions ①-⑥: ① The reaction temperature in step S1 is 158-165°C, and the reaction temperature in step S2 is 135-140°C; ② The reaction temperature in step S1 is 168-175°C, and the reaction temperature in step S2 is 115-120°C; ③ The reaction temperature in step S1 is 175-180°C, and the reaction temperature in step S2 is 105-110°C; ④ The reaction temperature in step S1 is 160-165°C, and the reaction temperature in step S2 is 85-90°C; ⑤ The reaction temperature in step S1 is 160-165°C, and the reaction temperature in step S2 is 80-90°C; ⑥ The reaction temperature in step S1 is 160-165°C, and the reaction temperature in step S2 is 105-110°C.

6. A polymer dispersant, characterized in that The polymer dispersant is obtained by the preparation method of the polymer dispersant as described in any one of claims 3 to 5.

7. An electrode slurry, characterized in that: It comprises an electrode material and the polymer dispersant according to any one of claims 1, 2 and 6.

8. The electrode slurry according to claim 7, characterized in that The electrode material is a carbon material or a carbon-coated material; Preferably, the carbon material is one or more of carbon nanotubes, graphene, acetylene black, porous carbon and conductive carbon black; Preferably, the carbon-coated material is one or both of carbon-coated lithium iron phosphate and carbon-coated lithium manganese iron phosphate; Preferably, the electrode slurry is any one of the systems ① and ②: ① The electrode slurry comprises: the polymer dispersant, the carbon material and the viscosity reducer; the mass ratio of the polymer dispersant, the carbon material and the viscosity reducer is preferably (2-8):1:(0.05-0.5), for example 4:1:0.1; ② The electrode slurry includes: the polymer dispersant, the carbon coating material, the binder and the conductive agent; the binder is preferably PVDF; the conductive agent is preferably carbon nanotubes, conductive carbon black or acetylene black; the mass ratio of the polymer dispersant, the carbon coating material, the binder and the conductive agent is preferably (0.2-0.8):173.70:(3-4):(2-3), for example 0.35:173.70:3.6:2.

7.

9. An electrode plate, characterized in that: The electrode is prepared using the electrode slurry as claimed in claim 7 or 8.

10. A battery, characterized in that: It includes the electrode plate as claimed in claim 9.

Citation Information

Patent Citations

  • Dispersing agent, preparation method and application of dispersing agent in preparation of carbon nanotube dispersion liquid

    CN115322293A